Identification of critical requirements for data recording of traceability in laying poultry: a study with farmers from the city of Bastos-SP (Research, Society and Development, 2020)
More demanding consumers pressure the food industry to attend the increasing demand for information. Traceability is a system that allows to gather information related to a product, from the beginning of its production chain to the moment of consumption. Data recording is the first stage of the Data Life Cycle, and supports the implementation of a system that is capable of tracking egg quality information. Egg is a widely consumed staple food and the Brazilian poultry production needs to be structured in order to attend quality and informational requirements. The aim of this paper is to identify the critical points of the traceability information gathering of eggs in commercial farms. The interviews carried for this paper allowed to validate the identified requirements, and to propose improvements in the process of collecting data of eggs. The steps of sanitary management in breeding and rearing, control of inputs, eggs collection, eggs classification and product identification were described as the critical steps for the implementation of traceability.